Sciascia on screen, tra pamphlet e thriller. Due riletture postume: ’Porte aperte’ e ’Una storia semplice’ - Marini, Alessandro (Incontri. Rivista europea di studi italiani, 2012)
Sciascia on Screen: Between pamphlet and thriller. Two Posthumous Re-readings: Porte aperte and Una storia semplice This essay treats two adaptations of Leonardo Sciascia’s novels, that, as they appeared soon after the author’s death, stand as a sort of literary memorial to the author: Porte aperte by Gianni Amelio, published in 1990, and Una storia semplice by Emidio Greco, from 1991. The intention is to highlight the original project of transposition from novel to film by means of the structural approach and the analysis of passages that are significant to the screenplay.